Proposal for a Histological Staging System of Mammary Carcinomas in Dogs and Cats. Part 2: Feline Mammary Carcinomas - Chocteau, Florian; Boulay, Marie-Mélanie; Besnard, Fanny; Valeau, Germain; Loussouarn, Delphine; Nguyen, Frédérique (Frontiers in Veterinary Science, 2019)
Background: Feline mammary carcinomas (FMCs) are characterized by a high frequency of metastatic spread. The clinical TNM (Tumor, Node, Metastasis) system is used to describe local, regional, and distant tumor extent within the patient, but few publications confirmed its association with survival in cats with FMC. The purpose of this study was to determine if the histological staging system proposed for dogs in part 1 of this article had significant association with prognosis in cats. Materials and Methods: This retrospective study included 395 female cats with a surgically removed mammary carcinoma, with a 2-year follow-up. Invasiveness (distinction between in situ and invasive FMCs), the pathologic tumor size (pT), lymphovascular invasion (LVI), and the pathologic nodal stage (pN) defined a 5-stage system: Stage 0 (FMCs in situ), Stage I (pT1, LVI–, pN0–pNX), Stage II (pT2, LVI–, pN0–pNX), Stage IIIA (pT1, LVI+ and/or pN+), and Stage IIIB (pT2, LVI+ and/or pN+), where pT1 was ≤20 mm, pT2 was >20 mm, and pNX corresponded to unsampled draining lymph node. Results: Higher histological stages were associated with reduced disease-free interval, overall survival, and specific survival. For cancer-specific survival, by univariate analysis (p<0.0001), median survival times and 1-year specific survival rates (1ySSR) were: stage 0 (1484 days; 1ySSR=85%; N=55; 14% of the cats), stage I (808 days; 1ySSR=76%; N=103; 26%), stage II (377 days; 1ySSR=51%; N=56; 14%), stage IIIA (448 days; 1ySSR=60%; N=83; 21%), and stage IIIB (207 days; 1ySSR=29%; N=98; 25%). The histological stages were also associated with specific survival by multivariate analysis (Hazard Ratio (HR)=2.72 for stage IIIB, HR=1.76 for stage IIIA, HR=1.50 for stage II compared with stage I), independently of Progesterone Receptor expression (HR=0.34 for PR+ compared with PR– FMCs) and tumor-associated inflammation (HR=1.33 when moderate to severe compared with absent to mild). Conclusion: A same histological staging system could be applied in dogs and cats with mammary carcinoma to refine prognosis assessment. In the near future, a preoperative complete tumor clinical staging and treatment based on the published standard of care should be performed in order to better validate the histological staging system here proposed.